KOMPUTERISASI TATA LETAK FASILITAS - Endro Prihastono (Jurnal Ilmiah Dinamika Teknik, 2014)
In general layout of the planned factory will also determine the efficiency and some things will also maintain the survival or success of an industrial workplace. computerized factory layout as a technique to be used in the process of allocation of territory. This technique is used to help out, check and encouraging results from design to determine the technique in determining the layout of the facility. Keywords : Facility Layout, Computerized.